A model for etching of three-dimensional high aspect ratio silicon structures in pulsed inductively coupled plasmas. (14th September 2018) - Wang, J-C; Tian, W; Rauf, S; Sadighi, S; Kenney, J; Stout, P; Vidyarthi, V S; Guo, J; Zhou, T; Delfin, K; Lundy, N; Pandey, S C; et al.
Abstract: A coupled plasma—feature scale model is employed to investigate the etching of high aspect ratio (HAR) silicon (Si) structures using a cyclic multi-step pulsed plasma process in an inductively coupled plasma (ICP) reactor. This process sequence includes an oxidation step to help protect the Si sidewalls, a main Si etch step where the ion energy and angular distribution (IEAD) and ion/neutral flux ratio are controlled through power pulsing, and a clean step prior to repeating the multi-step process. Two-dimensional plasma models are used to compute the IEAD as well as the fluxes of relevant ions and neutral radicals at the wafer. These plasma models are coupled to a three-dimensional feature scale model, where multiple cycles of the three-step etch sequence are simulated. The paper focuses on evaluation of several pulsing modes during the main Si etch step including separate pulsing of the ICP source or RF bias power, and their synchronized pulsing (with phase control). Process performance has been quantitatively evaluated by examining etch rates for Si and the SiO2 -like mask, Si/mask etch selectivity, and CDs within the HAR features. When only the RF bias power is pulsed, Si and mask etch rates scale with pulse duty cycle (DC). As a result, if Si is etched to the same depth, the HAR trenches are wider at higher DCs due to less total oxidation time and less protection of the sidewalls. ICP source power pulsing provides higher Si etch rate because of RF bias power being on continuously, but suffers from poor mask selectivity. Synchronized pulsing of both the ICP source and RF bias powers in conjunction with phase control provides additional flexibility in modulating the IEAD and the ion/neutral flux ratio. RF bias pulsing and in-phase synchronized pulsing yield the best selectivity for the conditions explored.